2018
DOI: 10.1093/bioinformatics/bty843
|View full text |Cite
|
Sign up to set email alerts
|

QuagmiR: a cloud-based application for isomiR big data analytics

Abstract: MicroRNAs (miRNAs) function as master regulators of gene expression. Recent studies demonstrate that miRNA isoforms (isomiRs) play a unique role in cancer development. Here, we present QuagmiR, the first cloud-based tool to analyze isomiRs from next generation sequencing data. Using a novel and flexible searching algorithm designed for the detection and annotation of heterogeneous isomiRs, it permits extensive customization of the query process and reference databases to meet the user 's diverse research needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…MicroRNA expression and 5’isomiR analysis were performed using QuagmiR on Amazon cloud instances through the Seven Bridges Genomics implementation of the NCI Cancer Genomics Cloud. QuagmiR is a customized Python scripts for the motif-based alignment and analysis of miRNA ( Bofill-De Ros et al, 2018 ). The analysis of The Cancer Genome Atlas (TCGA) was also performed using QuagmiR, with a previous conversion of the bam files to fastq files by Picard Sam-to-Fastq.…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNA expression and 5’isomiR analysis were performed using QuagmiR on Amazon cloud instances through the Seven Bridges Genomics implementation of the NCI Cancer Genomics Cloud. QuagmiR is a customized Python scripts for the motif-based alignment and analysis of miRNA ( Bofill-De Ros et al, 2018 ). The analysis of The Cancer Genome Atlas (TCGA) was also performed using QuagmiR, with a previous conversion of the bam files to fastq files by Picard Sam-to-Fastq.…”
Section: Methodsmentioning
confidence: 99%
“…into the mirGFF3 format. Furthermore, IsoMiRmap, miRge2 and QuagmiR[57], have been extended by their groups to output results directly to mirGFF3 format.This is a clear indication of the shorter adaptation time required for new standards originating from community-driven projects. mirtop operator can manage and compile mirGFF3 files allowing joining, filtering on single or multiple files, and transformation of the mirGFF3 information into a count matrix.…”
mentioning
confidence: 99%
“…More recently, other integrative approaches have addressed the detection of isomiRs and the potential functional influence that subtle modifications in the 3′ and 5′ boundaries of mature miRNA sequences might have on target recognition [88][89][90][91]. Other studies have also reported 5′ alternative processing events in a large number of miRNAs, contributing…”
Section: Discussionmentioning
confidence: 99%